Colorectal polyps and heterotrophic esophageal polyp of colon in a paediatric cohort in South India - R., Vishnu Abishek; Venkatakrishnan, L.; S., Mukundan (International Journal of Research in Medical Sciences, 2018)
Background: Clinical profile of polyps in paediatric cases are less in South India. Juvenile Polyps were the most common polyps in paediatric cases described in literature, presenting as LGI bleed. The aim of the study is to describe the clinical profile of colorectal polyps in paediatric population in a single tertiary care centre in South India. Methods: Paediatric cases between 0 and 16 years of age who underwent colonoscopy in our department from January 2002 to July 2018 were included from database. These cases were retrospectively analysed for presence of polyps, clinical presentation, indication for colonoscopy, histopathology of the resected polyps and other demographic details. Incomplete procedures were excluded. Results: About 166 paediatric cases underwent colonoscopy in the study period. 21 cases (12.65%) had colorectal Polyps. 85.7% of the polyps were in recto sigmoid region. Most common histological type was Juvenile Polyp (51.6%). One infant had sessile polyp in descending colon which was reported as heterotrophic esophageal mucosa in histopathology. LGI bleed was the most common presentation in children with polyps (66.6%). Conclusions: The prevalence of polyps in our cohort was 12.65%. Solitary Juvenile Polyp was the most common polyp in children, with lower GI bleed as the most common presenting feature. Rare case of heterotrophic esophageal polyp was seen in descending colon.